Decomposition and Oriented Growth of YBa2Cu3O7-x Films Prepared with Low Fluorine TFA-MOD Approach - Xiaohui Zhao; Pan Zhang; Yabing Wang; Jie Xiong; Bowan Tao (Advances in Condensed Matter Physics)
TFA-MOD approach of YBa2Cu3O7-x (YBCO) films has been approved to be the most promising method for mass production of low cost high temperature coated conductors. In order to reduce the decomposition time and improve the properties of YBCO films, copper propionate was used as the precursor and certain Lewis-bases were introduced into the precursor solution. The fluorine content of the solution was significantly reduced. High quality oriented YBCO films were prepared on LAO substrates with this low fluorine TFA-MOD approach. The effects of the sintering temperature on the oriented growth and properties of YBCO films were investigated. The preliminary results yielded the critical current density (Jc) of 2 MA/cm2 and critical current (Ic) of 120 A/cm width at 77 K and self-field.